English Pronunciation Teaching in Europe Survey: Selected results - Alice Henderson, Dan Frost, Elina Tergujeff, Alexander Kautszch, Deirdre Murphy, Anastazija Kirkova-Naskova, Ewa Waniek-Klimczak, David Levey, Una Cunningham, Lesley Curnick (Sciendo, De Gruyter, 2012)
This paper provides an overview of the main findings from a European-wide on-line survey of English pronunciation teaching practices. Both quantitative and qualitative data from seven countries (Finland, France, Germany, Macedonia, Poland, Spain and Switzerland) are presented, focusing on teachers' comments about: their own pronunciation, their training, their learners’ goals, skills, motivation and aspirations, and their preferences for certain varieties (and their perception of their students' preferences). The results of EPTiES reveal interesting phenomena across Europe, despite shortcomings in terms of construction and distribution. For example, most respondents are non-native speakers of English and the majority of them rate their own mastery of English pronunciation favourably. However, most feel they had little or no training in how to teach pronunciation, which begs the question of how teachers are coping with this key aspect of language teaching. In relation to target models, RP remains the variety of English which teachers claim to use, whilst recognizing that General American might be preferred by some students. Differences between countries are explored, especially via replies to open-ended questions, allowing a more nuanced picture to emerge for each country. Other survey research is also referred to, in order to contextualise the analyses and implications for teaching English and for training English teachers
EPTiES
Keywords: EPTiES, L2 pronunciation, teacher training, learner goals, learner skills, English variety preferences